2020
DOI: 10.3390/su12197956
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Climate Technology Centre and Network as a Climate Technology and Innovation Matchmaker for Developing Countries

Abstract: In this paper, the role of a matchmaker in transferring climate technologies to developing countries was explored from the perspective of open innovation. As the United Nations Framework Convention on Climate Change’s Technology Mechanism, the Climate Technology Centre and Network (CTCN) has strong convening power amongst the stakeholders who are responsible for climate actions in their country. Our research identified that the CTCN has successfully provided “4 openness” models (open network, open request for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 17 publications
1
32
0
Order By: Relevance
“…VM provides sustainability to be included in a construction project [21,116]. In the sustainability sense of construction firms, it was found that they face several obstacles as they mature and have a positive social, environmental and economic impact [117]. These firms should also search for swift and new means of sustaining customer confidence [107].…”
Section: Vm Activities Implementation For Building Sustainable Successmentioning
confidence: 99%
“…VM provides sustainability to be included in a construction project [21,116]. In the sustainability sense of construction firms, it was found that they face several obstacles as they mature and have a positive social, environmental and economic impact [117]. These firms should also search for swift and new means of sustaining customer confidence [107].…”
Section: Vm Activities Implementation For Building Sustainable Successmentioning
confidence: 99%
“…First, further global climate governance should facilitate network creation and matchmaking of climate change mitigation technology. The Climate Technology Centre and Network (CTCN), which was established under a Technology Mechanism to promote action on climate change technology development and transfer [1,63], has great potential for this role. As Lee and Mwebaza [63] mentioned, the CTCN's collaborative approach focuses on open innovation to facilitate diffusion of climate technologies based on developing countries' requests and attract technology experts and providers.…”
Section: Open Innovaiton and International Regimesmentioning
confidence: 99%
“…The Climate Technology Centre and Network (CTCN), which was established under a Technology Mechanism to promote action on climate change technology development and transfer [1,63], has great potential for this role. As Lee and Mwebaza [63] mentioned, the CTCN's collaborative approach focuses on open innovation to facilitate diffusion of climate technologies based on developing countries' requests and attract technology experts and providers. Thus, effective international regimes can expand their role as facilitators of open innovation by looking to existing institutions like CTCN as examples.…”
Section: Open Innovaiton and International Regimesmentioning
confidence: 99%
“…To assistance requests (Lee & Mwebaza, 2020). However, the empirical data collected in this research during the CTCN inception and its maturation period (2015)(2016)(2017)(2018)(2019)(2020) also indicate attempts to standardise and hence narrow, spaces for co-production of the technologybased solution in the case of modelling tools and hydro-climate technologies in South East Asia (Croxatto et al, 2020), where the transfer of technology packages was identified seeking replicability, not openness.…”
Section: Formal Global Knowledge Network In Environmental Governance?mentioning
confidence: 86%
“…However, the empirical data collected in this research during the CTCN inception and its maturation period (2015)(2016)(2017)(2018)(2019)(2020) also indicate attempts to standardise and hence narrow, spaces for co-production of the technologybased solution in the case of modelling tools and hydro-climate technologies in South East Asia (Croxatto et al, 2020), where the transfer of technology packages was identified seeking replicability, not openness. The recent evaluation provided by Lee and Mwebaza (2020) Findings strongly suggest that there is a growing demand for negotiating diverse kinds of knowledge in global environmental governance. In addition, technological advancements in ICT together with the maturation of formal global networks require that actors build on the coordination of functions in ways more inclusive than current approaches.…”
Section: Formal Global Knowledge Network In Environmental Governance?mentioning
confidence: 99%